EPIDEMIOLOGY AND PREVENTION OF MENINGOCOCCAL DISEASE: A CRITICAL APPRAISAL OF VACCINE POLICIES - Marco AP Safadi; E David G Mcintosh (Union of pediatricians of Russia, 2012)
Meningococcal disease is characterized by a marked variation in incidence and serogroup distribution by region and over time. In several European countries, Canada and Australia, immunization programs, including universal vaccination of infants or toddlers with catch-up campaigns in children and adolescents, aimed at controlling disease caused by meningococcal serogroup С have been successful in reducing disease incidence through direct and indirect protection. More recently, meningococcal conjugate vaccines targeting disease caused by serogroups A, C, W-135 and Y have been licensed and are being used in adolescent programs in the USA and Canada while a mass immunization campaign against serogroup A disease has been implemented in Africa. Positive results from clinical trials using vaccines against serogroup В disease in various age groups suggest the possibility of providing broader protection against serogroup В disease than is provided by the currently used outer membrane vesicle vaccines. The purpose of our review of meningococcal epidemiology and assessment of existing policies is to set the stage for future policy decisions. Vaccination policies to prevent meningococcal disease in different regions of the world should be based on quality information from enhanced surveillance systems.